A proposal for improvements of data vault ensemble process approach to retrieve big data: data vault limitations and optimization - Vissaram, Tahira Jéssica da Silva Ruivo (2020)
Dissertation presented as partial requirement for obtaining the master’s degree in Information Management, specialization in Information Systems and Technologies Management